Study of TiO2 Nanoparticles Surface Modification Approaches for Enhancing Photocatalytic Performance - NKENKU ANIMBOM BUMA CARL (The Graduate School, Ajou University, 2024)
Oxides such as TiO2 are promising materials for photocatalytic energy harvesting and environmental remediation, with significant potential for enhancing their photoactivity through the formation of heterojunctions, mixed phases, and controlled defects. This study explores various surface modification strategies to enhance the photocatalytic activity of TiO2, focusing on these approaches. Firstly, we synthesized SnS2/TiO2 heterojunction via a microwave-assisted hydrothermal process. SnS2 nanoparticles preferentially grew on nanocrystalline TiO2 nanosheets at the exposed {101} facets. This preferential growth facilitated charge separation through a direct Z-scheme mechanism, enhancing the photocatalytic degradation of organic dyes such as methylene blue (MB) and rhodamine B (RhB) compared to individual SnS2 or TiO2. The optimal SnS2 ratio of about 33% in the composites exhibited a high surface area (118.2 m²/g) and resulted in enhanced photodegradation rates. These results provide evidence of the beneficial effect of forming heterojunctions in enhancing the photoactivity of TiO2. In another approach, we synthesized TiO2@C composites through the pyrolysis of NH2-MIL-125, a metal-organic framework (MOF). The mixed-phase TiO2@C composite displayed excellent photocatalytic abilities in water splitting and RhB degradation, outperforming single-phase anatase and rutile TiO2@C composites. The composite with approximately 24% rutile phase showed the best photoactivity for hydrogen evolution and RhB photodegradation. The enhanced activity was attributed to efficient charge separation at the anatase-rutile interface and the contributions of the porous carbon matrix, which included increased surface area, extended light absorption, and prolonged charge carrier lifetime. Additionally, we investigated the role of controlled defects in TiO2 by preparing defect-controlled TiO2 nanosheets through thermal reduction with NaBH4 at 300°C. At this temperature, the amount of NaBH4 was systematically varied to increase the concentration of oxygen vacancies (OVs) at the surface, and the annealing time controlled the extent of bulk reduction. The optimal photocatalytic performance was achieved at a specific NaBH4 concentration, showing a volcano- shaped relationship between photocatalytic activity and defect density. The concentration of NaBH4 required for peak photoactivity is inversely correlated with annealing time, indicating that optimal photocatalytic activity requires a balanced distribution of surface and bulk defects. Our findings, supported by analyses of the relationships between photocatalytic activity and material characteristics such as bandgap, the paramagnetic states associated with defects, and the Eg shifts in Raman spectra, highlight the complex interplay of defects in enhancing the photoactivity in TiO2. This study demonstrates that forming heterojunctions, creating mixed-phase structures of TiO2, and controlling defects are effective strategies for enhancing the photocatalytic activity in TiO2.
학위논문(박사)--에너지시스템학과,2024. 8
Keywords: Defects; H2 evolution; NH2-MIL-125 (Ti); Oxygen vacancies; Photocatalysis; Photodegradation; SnS2; TiO2 nanosheet; TiO2/C